Impacts Of Climatic Changes On Paddy Production In Malaysia: Micro Study On Iada At North West Selangor - Mohd Ekhwan, Toriman; Mohd Mahmudul, Alam; Chamburi, Siwar; Basri, Talib (2014)
Climate change has mixed impacts on agriculture that differ among the areas, periods and crops. The changing factors of climate, especially rainfall and temperature, have been causing very strong negative impacts on Malaysian agriculture. Projection shows that the gap between current and potential yields will increase more in future that would lead to an unsustainable nature of agriculture in Malaysia. Based on the time series linear and log linear OLS regression model, this paper discusses the impacts of rainfall and temperature on the paddy sector by using the micro data of IADA at North West Selangor, Malaysia from 1992 to 2007. This study found that the output of micro data varies with the aggregate data and concludes that both temperature and rainfall have significant negative impacts on paddy production. It also provides policy recommendations and action plans to adapt and to cope properly with the changing nature of climate factors.